High-barrier packaging carton coating process and device based on biological mildew-proof coating

CN122880031APending Publication Date: 2026-10-09ANHUI RONGSHENG PACKAGING NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610993618.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明针对现有技术的上述不足,提供了一种基于生物防霉涂层的高阻隔性包装纸箱涂层工艺及装置,旨在解决现有技术中多层涂层易发生层间剥离,导致功能层失效的技术问题

Benefits of technology

[0025](1)本发明通过湿度梯度建立涂层内部的水化状态差异,驱动底层可迁移组分经由中间层三维连通孔隙网络向表层定向迁移,并在表层触发席夫碱交联反应,使涂层的交联密度在陈化处理过程中持续增加,阻隔性能在陈化后优于陈化前,克服了传统涂层阻隔性能随时间衰减的不足。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122880031A_ABST
    Figure CN122880031A_ABST
Patent Text Reader

Abstract

The application discloses a kind of coating method and device of composite coating for packaging carton.The method comprises: plasma treatment is carried out to paper base material;Bottom layer, intermediate layer and surface layer are coated in turn, bottom layer includes poly-γ-glutamic acid and dialdehyde starch, intermediate layer includes hydroxypropyl chitosan and porous starch microspheres, surface layer includes carboxymethyl chitosan and ε-polylysine;Segmented heating and curing;It is placed in the humidity gradient environment of high humidity of surface layer and low humidity of bottom layer and is aged again.In the aging process, the migratable component of bottom layer migrates to surface layer through the porous network of intermediate layer and forms Schiff base crosslinking with carboxymethyl chitosan, so that the coating is gradually densified.The device comprises a plasma treatment unit, three coating units and a drying unit, a segmented heating and curing channel, and a humidity gradient aging channel.The application has the advantages of continuously enhanced barrier performance, long effective period of mildew prevention, good interlayer bonding force, and suitability for continuous production of food and pharmaceutical packaging cartons.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Technology

[0002] This invention relates to the field of packaging materials technology, specifically to a coating process and apparatus for high-barrier packaging cartons based on a bio-resistant anti-mildew coating. Background Technology

[0003] With the advancement of replacing plastic with paper, the application of paper-based packaging materials in the food and pharmaceutical packaging fields continues to expand. However, the hydrophilicity and porous structure of paper-based materials themselves result in limited ability to block water vapor. In high humidity environments, they are prone to moisture absorption and deformation, and their mechanical properties deteriorate. At the same time, damp surfaces are conducive to the growth of microorganisms. These problems limit the application of paper-based packaging in scenarios with high requirements for barrier properties and hygiene.

[0004] To improve the barrier and anti-mildew properties of paper-based packaging, various technical solutions have been proposed. For example, Chinese patent CN119754096A discloses a high-performance corrugated cardboard box with waterproof and antibacterial functions and its preparation process. This is achieved by coating the surface of the corrugated cardboard substrate with a barrier-reinforcing coating and a composite antibacterial coating, thereby enhancing the waterproof and antibacterial properties of the cardboard box through the synergy of the two coatings. Chinese patent CN119434019B provides a barrier coating composition for paper-based materials, which uses a water-based acrylic prepolymer and chitosan-grafted polyvinyl alcohol, among other components, to impart water vapor and grease barrier properties while also providing antibacterial properties. Regarding mildew prevention, Chinese patent CN114575185B discloses a method for preparing a mildew-resistant packaging box, using nano-titanium dioxide and nano-zinc oxide as composite mildew-resistant materials coated onto the paper surface to form a mildew-resistant coating. In terms of sustained-release antibacterial properties, Chinese patent CN122169398A discloses a composite material for transporting and packaging Chinese medicinal materials that combines moisture absorption and sustained-release antibacterial functions. It loads a natural essential oil compound encapsulated with β-cyclodextrin into a porous starch-chitosan matrix to achieve long-lasting sustained-release antibacterial effects.

[0005] In existing technologies, multilayer coatings rely primarily on physical adsorption for bonding, resulting in insufficient interlayer bonding strength. This leads to easy delamination during carton folding, stacking, and transportation, causing functional layer failure. The release of anti-mold components is often characterized by rapid initial release followed by insufficient concentration later. While porous starch-loaded β-cyclodextrin inclusion complexes can achieve sustained release, single-stage sustained-release systems still struggle to maintain a stable and effective anti-mold concentration throughout the entire lifespan of the packaging material. The barrier performance of most coatings reaches its optimal level immediately after preparation, subsequently declining due to material aging and environmental humidity cycles, lacking a mechanism for spontaneous improvement in barrier performance during use. In existing multilayer coating systems, each functional layer is relatively independent, lacking a coupled design for interlayer material migration and chemical cross-linking, making it impossible to leverage environmental conditions to achieve synergistic enhancement between layers. Summary of the Invention

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-barrier packaging carton coating process and device based on a biological anti-mildew coating, which aims to solve the technical problem that multi-layer coatings are prone to interlayer peeling, leading to functional layer failure.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] This invention provides a high-barrier packaging carton coating process based on a bio-resistant anti-mildew coating, comprising the following steps:

[0009] (1) Low-temperature plasma treatment is performed on the paper-based material to be coated. The plasma treatment is carried out under normal pressure, using argon or a mixture of argon and oxygen as the working gas, with a treatment power of 150-350W and a treatment time of 15-35 seconds. After plasma treatment, polar groups such as hydroxyl and carboxyl groups are introduced into the surface of the paper-based material, and the surface water contact angle is reduced from 90°-110° before treatment to no more than 35°. The increase in surface polarity helps to enhance the interfacial bonding force between the subsequent coating and the paper-based material.

[0010] (2) The first coating composition is applied to the surface of the paper-based material treated in step (1), and a base layer is formed after drying. The first coating composition comprises, by weight, 100 parts of polyγ-glutamic acid, 60-100 parts of dialdehyde starch, 5-15 parts of ε-polylysine, 10-20 parts of glycerol, and 1000-1500 parts of deionized water. The weight-average molecular weight of polyγ-glutamic acid is 500,000-2,000,000 Da, and the aldehyde content of dialdehyde starch is 65%-85%. The carboxyl groups on the polyγ-glutamic acid molecular chain and the hydroxyl groups on the dialdehyde starch molecules form a physical cross-linking network through hydrogen bonds. The coating is applied by scraping, rolling, or slot extrusion coating, and the coating amount is 815 g / m³ on a wet weight basis. 2 After coating, the substrate is dried with hot air at 30–40°C for 3–6 minutes, resulting in a base coat thickness of 8–15 μm. The addition of ε-polylysine imparts initial antibacterial properties to the base coat.

[0011] (3) A second coating composition is applied to the surface of the base coating layer and dried to form an intermediate coating layer. The second coating composition comprises, by weight, 100 parts of hydroxypropyl chitosan, 25-45 parts of porous starch microspheres, 12-28 parts of citronellal / β-cyclodextrin inclusion complex, 3-8 parts of nanocellulose crystals, and 800-1200 parts of deionized water. The porous starch microspheres have an average particle size of 10-30 μm and a specific surface area of ​​80-200 m². 2 / g, with an average pore size of 0.5–3 μm; the inclusion rate of the citronellal / β-cyclodextrin inclusion complex is not less than 70%. This layer is applied by doctor blade coating, roller coating, or slot extrusion coating, with a coating weight of 35–60 g / m² on a wet weight basis. 2After coating, the mixture is first allowed to stand and level at 25–30°C for 3–6 minutes, then dried with hot air at 40–50°C for 8–15 minutes. The resulting intermediate layer coating has a thickness of 25–45 μm and a porosity of 20%–40%. The gaps between the porous starch microspheres and their own open-pore structure form a three-dimensional interconnected pore network in the coating. Citronellol / β-cyclodextrin inclusion complex is loaded into the pores of the porous starch microspheres and then embedded by a hydroxypropyl chitosan matrix, forming a two-stage sustained-release structure. The addition of nanocellulose crystals helps to improve the mechanical integrity of the coating.

[0012] (4) A third coating composition is applied to the surface of the intermediate layer coating, and after drying, a surface coating is formed. The third coating composition comprises, by weight, 100 parts of carboxymethyl chitosan, 8-20 parts of ε-polylysine, 6-12 parts of glycerol, and 900-1300 parts of deionized water. The degree of substitution of carboxymethyl chitosan is not less than 0.7. This layer is applied by scraping, rolling, or slot extrusion coating, and the coating amount is 8-14 g / m² on a wet weight basis. 2 After coating, the surface is dried with hot air at 30–40°C for 2–5 minutes, resulting in an initial coating thickness of 4–10 μm. The carboxymethyl chitosan molecule contains a large number of amino groups (-NH2), which can serve as active sites for subsequent cross-linking reactions; ε-polylysine gives the surface an immediate contact antibacterial and antifungal function.

[0013] (5) The paper-based material treated in steps (1) to (4) is sequentially heated and cured in three temperature ranges: 40-50℃, 60-70℃, and 80-90℃, for a total duration of 10-40 minutes. The treatment time in the 40-50℃ range is 4-8 minutes, which promotes the uniform evaporation of residual moisture in each layer and the initial shaping of the coating. The treatment time in the 60-70℃ range is 3-6 minutes, which promotes the interfacial bonding between porous starch microspheres and hydroxypropyl chitosan matrix and stimulates the segmental movement of polymer molecular chains. The treatment time in the 80-90℃ range is 1-4 minutes, which promotes the Schiff base reaction between the aldehyde groups on the dialdehyde starch molecules and the amino groups on the carboxymethyl chitosan and hydroxypropyl chitosan molecules, and initially establishes chemical crosslinking between the layers.

[0014] (6) The paper-based material cured in step (5) is placed in an environment with a humidity gradient along the coating thickness direction for aging treatment. The aging temperature is 25-40℃ and the aging time is 24-96 hours. The relative humidity of the environment on the surface side is 80%-90%, and the relative humidity of the environment on the bottom side is 50%-60%. The difference in humidity on both sides creates a water molecule concentration gradient along the thickness direction inside the coating. On the high humidity side (surface layer), the coating is in a higher degree of hydration, and the flexibility of the polymer molecular chains increases; on the low humidity side (bottom layer), the coating is less hydrated. This difference in hydration state drives some free or weakly bound polyγ-glutamic acid-dialdehyde starch complex components in the bottom layer coating to migrate towards the surface through the three-dimensional interconnected pore network composed of porous starch microspheres in the intermediate layer coating. The dialdehyde starch that migrates to the surface layer further undergoes a Schiff base crosslinking reaction with the amino groups of the carboxymethyl chitosan in the surface layer, which gradually increases the crosslinking density inside the coating and makes the structure more compact.

[0015] (7) The present invention also provides an apparatus for a high-barrier packaging carton coating based on a biological anti-mildew coating, comprising a frame, a horizontal conveying mechanism, a plasma pretreatment unit, a first coating unit, a first drying unit, a second coating unit, a second drying unit, a third coating unit, a third drying unit, a gradient activation curing channel, a humidity gradient aging channel, and a control system.

[0016] The horizontal conveying mechanism is mounted on the frame and includes a drive roller, a driven roller, a conveyor belt sleeved between the drive roller and the driven roller, and a servo motor that drives the drive roller to rotate.

[0017] The control system is electrically connected to the servo motor, plasma generator, each metering pump, third drying unit, humidification system and dehumidification system respectively;

[0018] The plasma pretreatment unit is located above the front end of the frame and includes a plasma generator, electrode plates, and a gas supply system. The electrode plates are arranged parallel to the conveyor belt above the frame.

[0019] The first coating unit, the second coating unit, and the third coating unit are sequentially arranged above the frame along the conveying direction. The first coating unit, the second coating unit, and the third coating unit each include a coating head, a feeding tank, and a metering pump. The feeding tank is connected to the inlet of the metering pump through a feeding pipe, and the outlet of the metering pump is connected to the coating head through a discharge pipe.

[0020] The first drying unit is located after the first coating unit, the second drying unit is located after the second coating unit, and the third drying unit is located after the third coating unit. Each drying unit includes a hot air box and a hot air circulation system.

[0021] The gradient activation and curing channel is located after the third drying unit and includes an activation chamber and a first heating zone, a second heating zone, and a third heating zone disposed within the activation chamber. The three heating zones are arranged sequentially along the conveying direction and their temperatures increase sequentially.

[0022] The humidity gradient aging channel is located after the gradient activation and curing channel, and includes an aging chamber, an upper humidification system, a lower humidification system, and a partition plate. The aging chamber is divided into two independent spaces, upper and lower, by the partition plate. The lower space is equipped with the lower dehumidification system, and the upper space is equipped with the upper humidification system.

[0023] (III) Beneficial Effects

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention establishes the difference in hydration state inside the coating by humidity gradient, drives the bottom migratable components to migrate directionally to the surface layer through the three-dimensional interconnected pore network of the intermediate layer, and triggers Schiff base crosslinking reaction on the surface layer, so that the crosslinking density of the coating continues to increase during the aging process, and the barrier performance is better after aging than before aging, overcoming the shortcomings of the traditional coating barrier performance decaying over time.

[0026] (2) ε-polylysine provides a rapid contact bactericidal effect, while citronellal / β-cyclodextrin inclusion complex provides a long-lasting sustained-release antibacterial effect through the rate-limited release of porous starch microspheres. The two antifungal mechanisms complement each other in terms of space (surface and middle layer) and action time (rapid and sustained release), which helps to extend the antifungal validity period.

[0027] (3) Schiff base crosslinking reaction forms chemical covalent bonds between the bottom layer and the surface layer. Compared with multilayer coating systems that rely solely on physical adsorption, the interlayer bonding strength is improved, which helps to reduce the risk of interlayer peeling during the use of the coating.

[0028] (4) The raw materials used in this invention, such as polyγ-glutamic acid, dialdehyde starch, hydroxypropyl chitosan, porous starch microspheres, carboxymethyl chitosan, ε-polylysine, citronellol, β-cyclodextrin, and nanocellulose, are all bio-based biodegradable materials that do not contain harmful chemically synthesized antifungal agents and heavy metal components, and are suitable for food and pharmaceutical packaging cartons. Attached Figure Description

[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0030] Figure 1 This is a schematic diagram of the preparation process of the present invention;

[0031] Figure 2 This is a schematic diagram of the structure of the cardboard box of the present invention;

[0032] Figure 3 This is a SEM image of the porous starch microsphere structure of the present invention;

[0033] Figure 4 This is a SEM image of the cross-sectional structure of the coating of the present invention;

[0034] Figure 5 This is the internal FTIR spectrum of the material of this invention;

[0035] Figure 6 This is a schematic diagram of the preparation device of the present invention;

[0036] Figure 7 This is a schematic diagram of the coating unit structure of the present invention;

[0037] Figure 8 This is a schematic diagram of the plasma pretreatment unit structure of the present invention;

[0038] Figure 9 This is a schematic diagram of the horizontal conveying mechanism of the present invention;

[0039] Figure 10 This is a schematic diagram of the drying unit structure of the present invention;

[0040] Figure 11 This is a schematic diagram of the gradient activation and curing channel structure of the present invention;

[0041] Figure 12 This is a schematic diagram of the humidity gradient aging channel structure of the present invention;

[0042] Figure 13 This is a schematic diagram of the cross-sectional structure of the humidity gradient aging channel of the present invention;

[0043] Figure 14 This is a schematic diagram of another embodiment of the humidity gradient aging channel of the present invention;

[0044] In the diagram: 1-Frame; 2-Horizontal conveying mechanism; 3-Plasma pretreatment unit; 4-First coating unit; 5-First drying unit; 6-Second coating unit; 7-Second drying unit; 8-Third coating unit; 9-Third drying unit; 10-Gradient activation and curing channel; 11-Humidity gradient aging channel; 12-Control system; 21-Driven roller; 22-Driven roller; 23-Conveyor belt; 24-Servo motor; 31-Plasma generator; 32-Electrode plate; 33-Gas supply system; 001-Coating head; 002-Feeding tank; 003-Metering pump; 01-Hot air box; 02-Hot air circulation system; 101-Activation chamber; 102-First heating zone; 103-Second heating zone; 104-Third heating zone; 111-Aging chamber; 112-Upper humidification system; 113-Lower dehumidification system; 114-Divider plate; 115-Fixing block; 116-Arc-shaped plate; 117-Discharge port of separator and arc-shaped plate; 100-Underlying coating; 200-Intermediate coating; 300-Top coating; 400-Paper-based material. Detailed Implementation

[0045] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0046] The present invention will be further described below with reference to embodiments.

[0047] This embodiment provides a method for applying a composite coating to packaging cartons.

[0048] 1. Formulation of coating compositions

[0049] First coating composition: Weigh 100g of polyγ-glutamic acid with a weight average molecular weight of 1.5 million Da, 80g of dialdehyde starch with an aldehyde content of 76.2%, 10g of ε-polylysine, and 15g of glycerol. Add deionized water to a total weight of 1200g, stir until completely dissolved, adjust the pH to 4.8 with glacial acetic acid, filter to remove insoluble matter, and set aside.

[0050] Second coating composition: Weigh 100g of hydroxypropyl chitosan, 35g of porous starch microspheres, 22g of citronellal / β-cyclodextrin inclusion complex, and 5g of nanocellulose crystals. Add deionized water to a total weight of 1000g, stir at high speed to disperse evenly, and set aside.

[0051] The third coating composition: Weigh 100g of carboxymethyl chitosan with a degree of substitution of 0.8, 15g of ε-polylysine, and 8g of glycerol, add deionized water to a total weight of 1100g, stir to dissolve evenly, and set aside.

[0052] 2. Coating method

[0053] The paper base material is three-layer AA grade corrugated cardboard with a basis weight of 650g / m². 2 Cut into sheets of 600mm x 400mm.

[0054] The complete process flow of this embodiment is as follows: Figure 1 As shown. Figure 1 In the process, the paper-based material first undergoes a plasma treatment process, followed by a first coating and drying process, a second coating and drying process, and a third coating and drying process. After completing the three coating layers, it enters a segmented heat curing process, and finally a humidity gradient aging process. The finished product is then discharged. The following is in order... Figure 1 The process is described step by step as shown.

[0055] S1: Plasma Processing

[0056] The paper-based material was placed with its inner surface facing upwards in a plasma treatment device. The treatment conditions were: power 250W, duration 25 seconds, working gas argon, flow rate 5L / min. After treatment, the water contact angle on the surface of the paper-based material decreased from approximately 100° to 28°, and the surface polarity was improved, which is beneficial for enhancing the interfacial adhesion between the subsequent coating and the paper-based material.

[0057] S2: First coating and drying – forming the undercoat

[0058] A first coating composition was applied to the surface of a plasma-treated paper-based material using a slot extrusion coating method, with a coating amount of 12 g / m² (wet weight). 2 After coating, it is dried with hot air at 35°C for 4 minutes to form the undercoat. This undercoat corresponds to... Figure 2 The 100 layers shown.

[0059] Figure 2 This is a cross-sectional schematic diagram of the final composite coating structure obtained in this embodiment. Figure 2 As shown, the inner surface of the paper-based material 400 is sequentially provided with a bottom coating 100, an intermediate coating 200, and a top coating 300. The bottom coating 100 has a thickness of 8-15 μm and is formed by drying the first coating composition. A physical cross-linking network is formed between polyγ-glutamic acid and dialdehyde starch through hydrogen bonds, and ε-polylysine imparts initial antibacterial ability to this layer.

[0060] S3: Second coating and drying – forming the intermediate layer coating

[0061] A second coating composition is applied to the surface of the base coating using a slot extrusion coating method, with a coating weight of 45 g / m² (wet weight). 2 After coating, allow to stand at 28°C for 4 minutes to level, then dry with hot air at 45°C for 10 minutes to form an intermediate layer coating. This intermediate layer coating corresponds to... Figure 2 The 200 layers shown.

[0062] like Figure 2 As shown, the intermediate coating 200 is located between the bottom coating 100 and the top coating 300, with a thickness of 25–45 μm. Hydroxypropyl chitosan serves as the matrix in this layer, and porous starch microspheres are dispersed within it. A scanning electron microscope image of the porous starch microspheres is shown below. Figure 3 As shown. From Figure 3 As can be clearly seen, the surface of the porous starch microspheres has a large number of openings with a pore size of approximately 0.5–3 μm. When these microspheres are stacked together in the coating, the gaps between the microspheres, together with the openings within the microspheres themselves, constitute a three-dimensional interconnected pore network. This pore network... Figure 2 The diagram schematically represents the voids between spherical particles. Citronellol / β-cyclodextrin inclusion complexes are loaded into the pores of porous starch microspheres and then embedded in a hydroxypropyl chitosan matrix, forming a two-stage sustained-release structure.

[0063] S4: Third coating and drying – forming the surface coating

[0064] A third coating composition is applied to the surface of the intermediate layer coating using a slot extrusion coating method, with a coating weight of 11 g / m² (wet weight). 2 After coating, it is dried with hot air at 35°C for 3 minutes to form a surface coating. This surface coating corresponds to... Figure 2 The 300 layers shown.

[0065] like Figure 2 As shown, the surface coating (300) is the outermost layer, with an initial thickness of 4–10 μm. Carboxymethyl chitosan molecules contain a large number of amino groups (-NH2), which can serve as active sites for subsequent cross-linking reactions; ε-polylysine endows the surface layer with contact antibacterial function, achieving rapid sterilization.

[0066] S5: Segmented heat curing

[0067] After the three-layer coating is completed, the paper-based material is fed into a segmented heating and curing channel, and treated sequentially at 45°C for 6 minutes, 65°C for 4 minutes, and 85°C for 2 minutes, for a total duration of 12 minutes. After curing, it is allowed to cool naturally to room temperature.

[0068] The 45℃ temperature zone promotes the uniform evaporation of residual moisture in each layer and the initial shaping of the coating; the 65℃ temperature zone promotes the interfacial bonding between porous starch microspheres and hydroxypropyl chitosan matrix and stimulates the segmental movement of polymer molecular chains; the 85℃ temperature zone promotes the Schiff base reaction between the aldehyde groups on the dialdehyde starch molecules and the amino groups on the carboxymethyl chitosan and hydroxypropyl chitosan molecules, and initially establishes chemical cross-linking between the layers.

[0069] S6: Humidity gradient aging

[0070] The cured paper-based material was placed in a humidity gradient aging channel for aging: the relative humidity of the environment on the surface coating (300) side was 85%, the relative humidity of the environment on the bottom coating (100) side was 55%, the temperature was 35℃, and the aging time was 48 hours.

[0071] The difference in humidity on both sides creates a water molecule concentration gradient along the thickness direction within the coating. The polymer molecular chains on the high-humidity side (surface layer) exhibit increased flexibility, while the low-humidity side (bottom layer) has a lower degree of hydration. This difference in hydration state drives the partially free or weakly bound polyγ-glutamic acid-dialdehyde starch complex in the bottom layer coating 100 through a three-dimensional interconnected pore network composed of porous starch microspheres in the intermediate layer coating 200. Figure 3 The starch migrates towards the surface coating in the 300 direction. The dialdehyde starch that migrates to the surface layer undergoes a Schiff base crosslinking reaction with the amino groups of the carboxymethyl chitosan in the surface layer, which gradually increases the crosslinking density inside the coating and makes the structure more compact.

[0072] After the above steps, the cross-section of the coating was observed using a scanning electron microscope, and the results are as follows: Figure 4 As shown. Figure 4 This is a scanning electron microscope (SEM) image of the cross-section of the composite coating obtained in this embodiment. From... Figure 4 The three-layer structure—bottom coating 100, intermediate coating 200, and top coating 300—can be clearly distinguished. The intermediate layer 200 shows a porous structure formed by porous starch microspheres. More importantly, from... Figure 4 It can be observed that the interfaces between the layers are tightly bonded, with no interlayer separation or microcracks, indicating that the bottom and top layers are chemically linked through Schiff base crosslinking, which improves the interlayer bonding strength. Meanwhile, the three-dimensional interconnected pore network in the intermediate layer retains a certain pore structure after aging, providing channels for the slow release of the antifungal components.

[0073] To verify the chemical nature of the cross-linking reaction during aging, infrared spectroscopy analysis was performed on the coating materials before and after aging. The results are as follows: Figure 5 As shown. Figure 5Curve A represents the infrared absorption spectrum of the coating material before aging (i.e., after step S5 and before step S6), and curve B represents the infrared absorption spectrum of the same coating material after aging for 48 hours (i.e., after step S6). Comparing curves A and B, the following changes can be observed:

[0074] At 1720 cm -1 At 1640 cm⁻¹, the absorption peak attributable to the stretching vibration of the aldehyde group (C=O) on the dialdehyde starch molecule shows a significant decrease in intensity from curve A to curve B, indicating that the number of aldehyde groups in the coating decreases during aging. -1 The absorption peak at the point is attributed to the stretching vibration of the imine bond (C=N) in the Schiff base reaction product. The intensity of the peak increases significantly from curve A to curve B, indicating that a large number of imine bonds are formed during the aging process.

[0075] The reduction of aldehyde groups and the increase of imine bonds occur simultaneously, forming a clear causal relationship—the aldehyde group on the dialdehyde starch molecule undergoes a Schiff base reaction with the amino group on the carboxymethyl chitosan molecule, consuming the aldehyde group while generating imine bonds. Figure 5 The infrared spectral data provide direct spectroscopic evidence for the continued Schiff base crosslinking reaction during aging. Furthermore, from... Figure 5 It can also be observed that 1600 cm -1 The bending vibration absorption peak attributable to amino (NH) also weakened after aging, which is consistent with the fact that amino groups were consumed as reactants.

[0076] comprehensive Figure 4 Cross-sectional morphology observation and Figure 5 Infrared spectral analysis confirmed that during the humidity gradient aging process (step S6), the polyγ-glutamic acid-dialdehyde starch complex in the bottom coating was transmitted through the three-dimensional interconnected pore network of the intermediate layer. Figure 3 ) migrates to the surface and undergoes a Schiff base cross-linking reaction with the amino groups of the surface carboxymethyl chitosan. Figure 5 This gradually densifies the coating structure. Figure 4 This allows for continuous improvement in barrier properties during the aging process. Performance Testing

[0077] The water vapor transmission rate test was conducted in accordance with GB / T 26253-2010, under the conditions of 38℃ and 90% relative humidity. The test results are shown in Table 1.

[0078] Table 1. Water vapor transmission rate test data.

[0079]

[0080] As a control, the water vapor transmission rate of the uncoated paper-based material under the same test conditions was 78.3 g / (m²). 2•24h).

[0081] The above results indicate that the water vapor permeability continues to decrease with the extension of aging time, suggesting that the barrier performance of the coating continues to improve during the aging process.

[0082] Oxygen permeability testing was conducted according to GB / T 19789-2005, under conditions of 23℃ and 50% relative humidity. After aging for 72 hours, the oxygen permeability of the sample was 5.8 cm⁻¹. 3 / (m 2 (24h, 0.1MPa); The oxygen permeability of the uncoated paper-based material under the same conditions was 186.5 cm⁻¹. 3 / (m 2 ·24h·0.1MPa).

[0083] Coating adhesion testing was conducted according to GB / T 9286-2021 (cross-cut test). After 72 hours of aging, the adhesion grade of the sample was 0 (the cut edges were completely smooth, with no cross-cuts falling off).

[0084] The anti-mold performance test was conducted in accordance with GB / T 4768-2008. The test conditions were a temperature of 28±2℃, a relative humidity of not less than 95%, and a culture time of 28 days. The mold grade of the sample was 0 (no mold growth was observed).

[0085] The test method for the anti-mildew effectiveness period is as follows: place the sample in a constant temperature and humidity chamber at a temperature of 28±2℃ and a relative humidity of 85%~90%, and observe and record the mildew level regularly. During the 18-month test period, the mildew level on the sample surface remains at level 0~1.

[0086] Control experiment

[0087] To verify the effects of humidity gradient aging treatment and polyγ-glutamic acid in this invention, the following control experiments were conducted. The paper base material, coating composition formulation, and coating steps for all control experiments were the same as in Example 1, with only the following variables changed. The aging time was 48 hours, and the water vapor transmission rate test conditions were the same as in Example 1.

[0088] Table 2 Results of the control experiment

[0089]

[0090] The method for determining the aldehyde content of the surface coating is as follows: take a sample of the surface coating and determine the aldehyde content by titration using the hydroxylamine hydrochloride method.

[0091] The results of control 1 show that, even with a humidity gradient, the surface aldehyde content was much lower in the absence of polyγ-glutamic acid than in the experimental group, indicating that the polyγ-glutamic acid-dialdehyde starch complex was the main form of substance that migrated.

[0092] The results of control 2 show that, under conditions without a humidity gradient (uniform humidity from top to bottom), the aldehyde content on the surface is significantly lower than that in the experimental group, indicating that a humidity gradient is a necessary condition for driving the directional migration of migratory components.

[0093] The results of control 3 show that the sample without humidity gradient aging treatment had the lowest aldehyde content on the surface, further illustrating that humidity gradient aging plays a key role in promoting the migration of migratory components to the surface and their participation in cross-linking reactions.

[0094] Example 2

[0095] The difference between this embodiment and Embodiment 1 lies in the different raw material ratios and process parameters.

[0096] The first coating composition is formulated as follows: 100g of polyγ-glutamic acid with a weight average molecular weight of 2 million Da, 90g of dialdehyde starch with an aldehyde content of 78%, 12g of ε-polylysine, 18g of glycerol, and deionized water to a total weight of 1300g.

[0097] The second coating composition is formulated as follows: 100g of hydroxypropyl chitosan, 40g of porous starch microspheres, 25g of citronellal / β-cyclodextrin inclusion complex, 6g of nanocellulose crystals, and deionized water to a total weight of 1100g.

[0098] The third coating composition is formulated as follows: 100g of carboxymethyl chitosan with a degree of substitution of 0.75, 18g of ε-polylysine, 10g of glycerol, and deionized water to a total weight of 1200g.

[0099] The plasma treatment conditions were: power 300W, duration 30 seconds.

[0100] Coating amounts were: base coat 14g / m² 2 (Wet weight), intermediate layer 50g / m 2 (Wet weight), surface layer 13g / m 2 (wet weight).

[0101] The segmented heat curing conditions are: 48℃ for 6 minutes, 68℃ for 4 minutes, and 88℃ for 2 minutes, for a total of 12 minutes.

[0102] The humidity gradient aging conditions were: 88% relative humidity on the surface, 50% relative humidity on the bottom, 38℃, and 72 hours of aging.

[0103] Tests showed that the water vapor transmission rate of the sample prepared in this embodiment was 7.8 g / (m²) after aging for 72 hours. 2 • 24h), oxygen permeability was 4.5 cm. 3 / (m 2·24h·0.1MPa), mildew resistance level is 0, adhesion level is 0.

[0104] Example 3

[0105] This embodiment provides an apparatus for implementing the high-barrier packaging carton coating process based on a bio-resistant anti-mildew coating as described in Embodiment 1. The structure of the apparatus is as follows:

[0106] like Figure 6 As shown, the device includes a frame 1, a conveying mechanism 2, a plasma treatment unit 3, a first coating unit 4, a first drying unit 5, a second coating unit 6, a second drying unit 7, a third coating unit 8, a third drying unit 9, a segmented heating and curing channel 10, a humidity gradient aging channel 11, and a control system 12.

[0107] like Figure 6 and Figure 9 As shown, the conveying mechanism 2 is mounted on the frame 1 and includes a drive roller 21, a driven roller 22, a conveyor belt 23 sleeved between the drive roller 21 and the driven roller 22, and a drive motor 24 that drives the drive roller 21 to rotate. The upper surface of the conveyor belt 23 is used to carry the paper-based material and convey it sequentially through each processing station in a horizontal direction.

[0108] like Figure 6 and Figure 8 As shown, the plasma processing unit 3 is located above the front end of the frame 1 and before the first coating unit 4, and includes a plasma generator 31, an electrode plate 32, and a gas supply system 33. The electrode plate 32 is arranged parallel to the conveyor belt 23 above it, and the gap between the electrode plate 32 and the conveyor belt 23 allows the paper-based material to pass through. The plasma generator 31 is used to generate dielectric barrier discharge, and the gas supply system 33 is used to supply working gas to the discharge gap between the electrode plate 32 and the paper-based material.

[0109] like Figure 6 As shown, the first coating unit 4, the second coating unit 6, and the third coating unit 8 are sequentially arranged above the frame 1 along the conveying direction, and are used to coat the first, second, and third coating compositions, respectively. Figure 7 As shown, each coating unit includes a coating head 001, a storage tank 002, and a metering pump 003. The storage tank 002 is connected to the inlet of the metering pump 003 via a pipe, and the outlet of the metering pump 003 is connected to the coating head 001 via a pipe. The coating head 001 is positioned above the conveyor belt 23, and the gap between its lower end and the upper surface of the conveyor belt 23 can be adjusted according to the thickness of the paper base material.

[0110] like Figure 6 and Figure 10As shown, the first drying unit 5 is located after the first coating unit 4, the second drying unit 7 is located after the second coating unit 6, and the third drying unit 9 is located after the third coating unit 8. Each drying unit includes a hot air box 01 and a hot air circulation system 02. The hot air box 01 is positioned above the conveyor belt 23, and the hot air circulation system 02 generates hot air and sends it into the hot air box 01.

[0111] like Figure 6 and Figure 11 As shown, the segmented heating and curing channel 10 is located after the third drying unit 9, and includes a curing channel housing 101 and three heating zones 102, 103, and 104 located within the curing channel housing 101. The three heating zones are arranged sequentially along the conveying direction, with the set temperatures of each zone increasing sequentially: the temperature range of the first heating zone 102 is 40–50°C, the temperature range of the second heating zone 103 is 60–70°C, and the temperature range of the third heating zone 104 is 80–90°C. Each heating zone is equipped with an independent heating element and a temperature sensor.

[0112] like Figure 6 and Figure 13As shown, the humidity gradient aging channel 11 is located after the segmented heating and curing channel 10, and includes an aging channel box 111, a humidification device 112, a dehumidification device 113, and a partition member 114. The partition member 114 divides the inner cavity of the aging channel box 111 into an upper chamber and a lower chamber. The upper chamber is equipped with the humidification device 112 to control the relative humidity of the upper chamber at 80% to 90%; the lower chamber is equipped with the dehumidification device 113 to control the relative humidity of the lower chamber at 50% to 60%. The partition member 114 is mesh-like, and the cardboard box 400 is placed on the partition member 114, which can isolate the airflow between the upper chamber and the lower chamber of the aging channel box 111. Arc-shaped plates 116 are symmetrically fixed on both sides of the partition member 114. Fixing blocks 115 are fixed on both side walls of the humidity gradient aging channel 11. The partition member 114 rests on the fixing blocks 115 through the arc-shaped plates 116. One end of the humidity gradient aging channel 11 is provided with a partition member and arc-shaped plate outlet 117. The inner height of the arc-shaped plate 116 is higher than the height of the partition member 114, and the height of the partition member 114 and the arc-shaped plate 116 is lower than the height of the partition member and arc-shaped plate outlet 117. When the box cardboard 400 is placed on the partition member 114, the two sides of the box cardboard 400 are in close contact with the inner and outer sides of the arc-shaped plate 116. Therefore, the inner side of the arc-shaped plate 116 plays a positioning role. In addition, the arc-shaped plate 116, the box cardboard 400 and the fixing blocks 115 isolate the upper chamber and the lower chamber of the humidity gradient aging channel 11, preventing the upper chamber and the lower chamber from being blocked from humidity convection. Because the humidity in the upper chamber of this invention reaches 80% to 90%, which is very high, water easily accumulates on the inner wall of the humidity gradient aging channel 11. The water droplets slide down the inner wall of the humidity gradient aging channel 11 and land in the arc-shaped groove of the arc-shaped plate 116. The arc-shaped groove collects the water, preventing it from flowing directly onto the sides of the cardboard box 400. Furthermore, the arc-shaped plate 116 has the ability to undergo lateral elastic deformation. When the arc-shaped plate 116 is placed on the fixing block 115, its elastic deformation increases the pressure on the fixing block 115, resulting in high strength. The fixing block 115 can be made of hard rubber, and it also provides better sealing. The arc-shaped plate 116 and the partition member 114 can be slightly lifted from the fixing block 115 and removed from the outlet 117 of the partition member and arc-shaped plate. This facilitates the inspection and maintenance of the partition member and the arc-shaped plate 116, and also facilitates installation without the need for fasteners. The separator and the arc-shaped plate outlet 117 also facilitate the drainage of water accumulated on the arc-shaped plate 116.

[0113] like Figure 14As shown, in another embodiment of the humidity gradient aging channel 11, the arc-shaped plate 116 is made of steel sheet material with high elasticity, and the separator 114 is made of steel with high hardness and strength. The arc-shaped plate 116 and the separator 114 are set separately. Specifically, a slot 118 is provided on the outer side of the inner side of the arc-shaped plate 116 corresponding to the end of the separator 114. The outer side of the separator 114 is inserted into the slot 118. The outer side of the arc-shaped plate 116 is fixedly connected to the fixing block 115. Due to the high elasticity of the arc-shaped plate 116, separators 114 of different widths can be inserted between the arc-shaped plates 116, thereby adapting to carton substrates 400 of different widths without affecting other functions of the arc-shaped plate 116. The width of one end of the arc-shaped plate 116 is greater than the width of the other side, so the distance between the two arc-shaped plates 116 is large at one end and small at the other end. The separator 114 can be inserted from the end with the larger distance between the two arc-shaped plates 116, which facilitates the installation of the separator 114.

[0114] The control system 12 is electrically connected to the drive motor 24, the plasma generator 31, the metering pump 003 of each coating unit, the hot air circulation system 02 of each drying unit, the heating zone of the segmented heating curing channel 10, and the humidification device 112 and dehumidification device 113 of the humidity gradient aging channel 11, respectively, and is used to control the operating status and process parameters of each device.

[0115] The device operates as follows:

[0116] Sheets of paper-based material are placed one by one at the front feed end of conveyor belt 23, with the inner surface of the paper-based material facing upwards. Conveyor belt 23 runs at a set speed under the drive of drive motor 24, conveying the paper-based material backwards.

[0117] The paper-based material first enters the plasma processing unit 3. When it passes under the electrode plate 32, the low-temperature plasma generated by the plasma generator 31 treats the surface of the paper-based material and introduces polar groups on its surface.

[0118] Subsequently, the paper-based material sequentially enters the first coating unit 4 and the first drying unit 5. The metering pump 003 of the first coating unit 4 quantitatively delivers the first coating composition from the storage tank 002 to the coating head 001, which uniformly coats the coating composition onto the surface of the paper-based material. The coated paper-based material then enters the first drying unit 5, where it is dried by hot air in the hot air box 01 to form the undercoat.

[0119] Next, the paper-based material enters the second coating unit 6 and the second drying unit 7 in sequence, where the second coating composition is coated and dried to form an intermediate layer coating.

[0120] Then the paper-based material enters the third coating unit 8 and the third drying unit 9 in sequence, where the third coating composition is applied and dried to form a surface coating.

[0121] After the paper-based material has completed three layers of coating and preliminary drying, it enters the segmented heating and curing channel 10 and passes through the first heating zone 102, the second heating zone 103 and the third heating zone 104 in sequence to complete the segmented heating and curing process.

[0122] Finally, the paper-based material enters the humidity gradient aging channel 11. As the paper-based material travels through the channel, its upper surface coating side is exposed to the high humidity environment of the upper chamber, while its lower surface bottom coating side is exposed to the low humidity environment of the lower chamber. This creates a stable humidity gradient in the coating thickness direction, thus completing the aging process.

[0123] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-barrier packaging carton coating process and apparatus based on a biological anti-mildew coating, characterized in that, Includes the following steps: (1) The paper-based material to be coated is subjected to low-temperature plasma treatment, and the water contact angle of the treated surface is not greater than 35°; (2) A first coating composition is applied to the surface of the paper-based material after step (1), and a bottom coating is formed after drying; the first coating composition contains polyγ-glutamic acid, dialdehyde starch and ε-polylysine, wherein polyγ-glutamic acid and dialdehyde starch form a physical cross-linking network through hydrogen bonds; (3) A second coating composition is applied to the surface of the bottom coating and dried to form an intermediate coating; the second coating composition contains hydroxypropyl chitosan and porous starch microspheres, wherein the porous starch microspheres form a three-dimensional interconnected pore structure in the intermediate coating. (4) A third coating composition is applied to the surface of the intermediate layer coating and dried to form a surface coating; the third coating composition contains carboxymethyl chitosan and ε-polylysine; (5) The paper-based material treated in steps (1) to (4) is sequentially heated and cured in three temperature ranges: 40-50℃, 60-70℃ and 80-90℃. (6) The paper base material cured in step (5) is placed in an environment with a humidity gradient along the coating thickness direction for aging treatment, wherein the relative humidity of the environment on the surface side is higher than that on the bottom side.

2. The method according to claim 1, characterized in that, In step (2), the weight parts of each component in the first coating composition are: 100 parts of polyγ-glutamic acid, 60-100 parts of dialdehyde starch, 5-15 parts of ε-polylysine, 10-20 parts of glycerol, and 1000-1500 parts of deionized water; the weight average molecular weight of the polyγ-glutamic acid is 500,000 to 2,000,000 Da; and the aldehyde content of the dialdehyde starch is 65% to 85%.

3. The method according to claim 1, characterized in that, In step (3), the weight parts of each component in the second coating composition are as follows: 100 parts hydroxypropyl chitosan, 25-45 parts porous starch microspheres, 12-28 parts citronellal / β-cyclodextrin inclusion complex, 3-8 parts nanocellulose crystals, and 800-1200 parts deionized water; the average particle size of the porous starch microspheres is 10-30 μm, and the specific surface area is 80-200 m². 2 / g, with an average pore size of 0.5–3 μm.

4. The method according to claim 1, characterized in that, The weight parts of each component in the third coating composition in step (4) are: 100 parts of carboxymethyl chitosan, 8-20 parts of ε-polylysine, 6-12 parts of glycerol, and 900-1300 parts of deionized water; the degree of substitution of the carboxymethyl chitosan is not less than 0.

7.

5. The method according to claim 1, characterized in that, The total time for the segmented heating and curing in step (5) is 10 to 40 minutes, of which the treatment time in the 40 to 50°C range is 4 to 8 minutes, the treatment time in the 60 to 70°C range is 3 to 6 minutes, and the treatment time in the 80 to 90°C range is 1 to 4 minutes.

6. The method according to claim 1, characterized in that, The aging process in step (6) is carried out at a temperature of 25-40°C for 24-96 hours; the relative humidity of the environment on the surface side is 80%-90% and the relative humidity of the environment on the bottom side is 50%-60%.

7. An apparatus for implementing the high-barrier packaging carton coating based on a bio-anti-mildew coating as described in any one of claims 1-6, characterized in that, It includes a frame (1), a horizontal conveying mechanism (2), a plasma pretreatment unit (3), a first coating unit (4), a first drying unit (5), a second coating unit (6), a second drying unit (7), a third coating unit (8), a third drying unit (9), a gradient activation curing channel (10), a humidity gradient aging channel (11), and a control system (12).

8. The coating apparatus for the coating process according to claim 7, characterized in that, The horizontal conveying mechanism (2) is mounted on the frame (1) and includes a drive roller (21), a driven roller (22), a conveyor belt (23) sleeved between the drive roller (21) and the driven roller (22), and a servo motor (24) that drives the drive roller (21) to rotate. The control system (12) is electrically connected to the servo motor (24), plasma generator (31), each metering pump (003), third drying unit (9), humidification system (112) and dehumidification system (113), respectively; The plasma pretreatment unit (3) is located above the front end of the frame (1) and includes a plasma generator (31), an electrode plate (32) and a gas supply system (33). The electrode plate (32) is arranged parallel to the conveyor belt (23) above it. The first coating unit (4), the second coating unit (6) and the third coating unit (8) are arranged sequentially above the frame (1) along the conveying direction. The first coating unit (4), the second coating unit (6) and the third coating unit (8) respectively include a coating head (001), a feeding tank (002) and a metering pump (003). The feeding tank (002) is connected to the inlet of the metering pump (003) through a feeding pipe. The outlet of the metering pump (003) is connected to the coating head (001) through a discharge pipe. The first drying unit (5) is located after the first coating unit (4), the second drying unit (7) is located after the second coating unit (6), and the third drying unit (9) is located after the third coating unit (8). Each drying unit includes a hot air box (01) and a hot air circulation system (02).

9. The apparatus according to claim 7, characterized in that, The gradient activation and curing channel (10) is located after the third drying unit (9) and includes an activation chamber (101) and a first heating zone (102), a second heating zone (103) and a third heating zone (104) located in the activation chamber (101). The three heating zones are arranged sequentially along the conveying direction and their temperatures increase sequentially.

10. The apparatus according to claim 7, characterized in that, The humidity gradient aging channel (11) is located after the gradient activation and curing channel (10), and includes an aging box (111), an upper humidification system (112), a lower humidification system (113), and a partition plate (114). The aging box (111) is divided into upper and lower independent spaces by the partition plate (111). The lower space is equipped with the lower dehumidification system (113), and the upper space is equipped with the upper humidification system (112). The partition member (114) is mesh-like, and the box cardboard 400 is placed on the partition member (114), which allows the upper chamber of the aging channel box (111) to be open. Airflow is separated from the lower chamber; arc-shaped plates (116) are symmetrically fixed on both sides of the partition member (114), and fixed blocks (115) are fixed on both sides of the humidity gradient aging channel (11). The partition member (114) rests on the fixed blocks (115) through the arc-shaped plates (116). A partition member and arc-shaped plate outlet (117) is provided at one end of the humidity gradient aging channel (11). The inner height of the arc-shaped plate (116) is higher than the height of the partition member (114), and the height of the partition member (114) and the arc-shaped plate (116) is lower than the height of the partition member and arc-shaped plate outlet (117).

Citation Information

Patent Citations

  • A method for preparing a mildew-proof packaging carton

    CN114575185B

  • Barrier coating composition for paper-based material, barrier coating and paper substrate

    CN119434019B

  • High-performance corrugated carton with waterproof and antibacterial functions and preparation process of high-performance corrugated carton

    CN119754096A

  • Traditional Chinese medicinal material transportation and packaging composite material with moisture absorption and slow-release bacteriostasis functions and preparation method of traditional Chinese medicinal material transportation and packaging composite material

    CN122169398A